The measurement and modelling of low-pressure phase equilibrium data for 1-alcohols + n-alkanes - du Plessis, Susanna Hendrina (Stellenbosch : Stellenbosch University, 2022)
Thesis (MEng)--Stellenbosch University, 2022.